KAWIN BOTE (NIKAH PAKSA) DALAM PERSPEKTIF HUKUM ISLAM DI KECAMATAN ADONARA KABUPAKTEN FLORES TIMUR PROVINSI NUSA TENGGARA TIMUR - Hendryani Hasri Ainun; Nur Hasan; Fathurrahman Alfa Alfa (Jurnal Hikmatina, 2022)
AbstrakThis research is entitled "kawin bote (forced marriage) in the perspective of Islamic law (case study in Adonara District)". And this research is a field research (filed research). The limitations of the problems discussed are forced marriages that occurred in 2013 to 2020 with the formulation of the problem, what factors encourage forced marriages, how is the impact of forced marriages, what is the perspective of Islamic law on the problem. Therefore, the purpose of this research is is to find out about forced marriage, the factors that encourage it, its impact and an overview of Islamic law. While the method of data collection in this study was through observation and interviews with the research subjects were the people of the Adonara sub-district who lived in the Oringbele village and knew about forced marriages. The object of this research is bote marriage (forced marriage) in Adonara sub-district which occurred from 2013 to 2020, the method of data analysis is to use analytical techniques using qualitative analysis techniques.Keyword : Bote Marriage, Islamic Law Perspective,Hukum Islam